Thermodynamic properties of flufenamic ionic liquids - Romeli, F.J. (Trans Tech Publications Ltd, 2014)
Active pharmaceutical ingredients-ionic liquids (APIs-ILs) in which, when compared to active pharmaceutical ingredients hydrochloride (APIs-HCl), exhibits better solubility, increased thermal stability and significant enhancement in the efficiency of APIs. Three novel flufenamic-ILs were synthesized and their density and viscosities were determined and reported as a function of temperature. From the experimental density data the crystal energy, molecular volume and standard entropy was estimated. The result showed that the density and viscosities decrease with increasing temperature in these four ionic liquids. Â© 2014 Trans Tech Publications, Switzerland.